Social-environmental factors and cognitive and behavioral functioning in pediatric sickle cell disease. Issue 1 (2nd January 2020) - Bills, Sarah E.; Schatz, Jeffrey; Hardy, Steven J.; Reinman, Laura
ABSTRACT: Sickle cell disease (SCD), an inherited blood disorder that primarily affects individuals of African descent, is associated with serious medical complications as well as numerous social-environmental risk factors. These social-environmental factors are linked to long-standing social inequities, such as financial hardship and racial discrimination, both of which impact cognitive and behavioral functioning in youth. Previous research on the relationship between social-environmental risk and psychological functioning has primarily relied on non-modifiable, unidimensional measures of socioeconomic status (SES), such as income and parental education, as a proxy for social-environmental risk. The current study aimed to address the limitations associated with typical SES-type measures by comparing the unique and shared association of SES and more targeted and modifiable social-environmental factors (e.g., parent and family functioning) with specific areas of cognitive and behavioral adjustment in pediatric SCD. Seventy children ages 4–8 years old and their parents completed measures of social-environmental risk and psychological adjustment. Exploratory factor analysis indicated parent and family functioning measures were largely independent of SES. Parent and family functioning predicted phonological processing and ADHD symptoms above and beyond SES alone. In addition, the predictive ability of social-environmental risk factors appears to vary by genotype severity for measures of social functioning and math problem-solving ability. Future studies are needed to explore more specific and well-supported models of modifiable social-environmental risk and the relative impact of social-environmental risk on cognitive and behavioral functioning.